Business intelligence for medical appointments at Hospital Nuestra Señora the Lourdes at Argelia Cauca - Gutiérrez Idrobo, Daniela Iboth; Realpe Grijalba, Edwin Mauricio; Vejarano Sánchez, Luis Alfonso; Varona Taborda, María Alejandra (SATHIRI, 2020)
This paper presents a solution based on Business Intelligence with the purpose of generating a prototype of analysis and interpretation of the data of medical appointments of the existing systems in the Hospital Nuestra Señora de Lourdes in the municipality of Argelia in the department of Cauca, where the growing need for integrated medical care has led organizations to adopt comprehensive support systems for handling large volumes of data that need to be attended and processed quickly and efficiently to guarantee excellence in service provision, These entities, especially those of the public sector, must make decisions aimed at satisfying the demand for services of patients who attend health centers. Using the Hefesto methodology that was adapted to the requirements promoting the proper development and analysis of the data and a data warehouse was built that allowed the generation of reports to provide better service to the patient, medical staff and administrative.